The Effectiveness of the Complete Systematic Land Registration Program (PTSL) in Increasing Legal Certainty Over Land - Hilmi, Faisal; Sri Darmadi, Nanang (TABELLIUS: Journal of Law, 2025)
This study aims to analyze: 1) The effectiveness of the implementation of Complete Systematic Land Registration (PTSL) in increasing legal certainty over land in Indramayu Regency. 2) Obstacles and solutions to the implementation of PTSL in increasing legal certainty over land in Indramayu Regency. This type of research is empirical legal research. The approach method in this research is sociological juridical. The types of data in this research are primary and secondary data. The data collection method uses observation techniques, interviews and library techniques (document study). The analysis in this research is descriptive qualitative. The results of the study concluded: 1) The effectiveness of the implementation of Complete Systematic Land Registration (PTSL) in increasing legal certainty over land in Indramayu Regency is reflected in its systematic implementation. The effectiveness of PTSL in Indramayu Regency is realized through the integration of a strong and coordinated legal structure, clear and adaptive legal substance as regulated in the UUPA, PP Number 18 of 2021, and Permen ATR/BPN Number 6 of 2018, as well as a legal culture of the community that is increasingly aware of the importance of certainty and legality of land rights. The synergy of the three elements of the legal system makes the implementation of PTSL effective in strengthening legal certainty, protection of land rights, and orderly land administration in Indramayu Regency. 2) Obstacles in the Implementation of Complete Systematic Land Registration (PTSL) in Increasing Legal Certainty on Land in Indramayu Regency include technical obstacles in the form of inaccurate data and limited officers, legal obstacles in the form of incomplete ownership documents and land boundary disputes, and social obstacles in the form of low public awareness and participation. The solution is carried out through digitalization of the land system, increasing the capacity of officers, administrative clarification, and strengthening public outreach and participation.